2023
DOI: 10.3389/fneur.2022.1105592
|View full text |Cite
|
Sign up to set email alerts
|

Decreased degree centrality values as a potential neuroimaging biomarker for migraine: A resting-state functional magnetic resonance imaging study and support vector machine analysis

Abstract: ObjectiveMisdiagnosis and missed diagnosis of migraine are common in clinical practice. Currently, the pathophysiological mechanism of migraine is not completely known, and its imaging pathological mechanism has rarely been reported. In this study, functional magnetic resonance imaging (fMRI) technology combined with a support vector machine (SVM) was employed to study the imaging pathological mechanism of migraine to improve the diagnostic accuracy of migraine.MethodsWe randomly recruited 28 migraine patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“… Jorge-Hernandez et al (2014) developed a set of machine learning algorithms through graph theory analysis, demonstrating that the classification accuracies of migraine patients using NN and SVM classifiers were 92.86% and 87%, respectively. Wang Q. et al (2022) combined degree centrality (DC) and SVM analysis, revealing a significant decrease in the DC values of the bilateral inferior temporal gyrus (ITG) among migraine sufferers. A positive linear correlation was found between the left ITG and MIDAS scores.…”
Section: The Role Of Fmri Technology In Diagnosing Primary Headachesmentioning
confidence: 99%
“… Jorge-Hernandez et al (2014) developed a set of machine learning algorithms through graph theory analysis, demonstrating that the classification accuracies of migraine patients using NN and SVM classifiers were 92.86% and 87%, respectively. Wang Q. et al (2022) combined degree centrality (DC) and SVM analysis, revealing a significant decrease in the DC values of the bilateral inferior temporal gyrus (ITG) among migraine sufferers. A positive linear correlation was found between the left ITG and MIDAS scores.…”
Section: The Role Of Fmri Technology In Diagnosing Primary Headachesmentioning
confidence: 99%
“…Neuroimaging techniques combined with psychological scales, have been extensively employed in investigating structural and functional brain disorders (Gao et al, 2022 , 2023 ; Wang et al, 2022 ; Zhong et al, 2023a ). Meng et al found that abnormal connectivity patterns were observed in the left middle temporal gyrus in GAD, underscoring the significance of GAD pathophysiology.…”
Section: Psychological Scales and Brain Imagingmentioning
confidence: 99%
“…Unlike task-based fMRI analyses, rs-fMRI permits the evaluation of individuals not performing complex tasks and is thus better suited to the assessment of individuals unable to complete cognitively demanding tasks due to neurological or psychiatric disorders (Takamura and Hanakawa, 2017). For these reasons, fMRI had been used to study patients with a range of diseases and disorders, including depression (Guo et al, 2022), bipolar disorder (Vargas et al, 2013), schizophrenia (Whitfield-Gabrieli et al, 2009), epilepsy (Gao et al, 2022b, attention deficit hyperactivity disorder, abnormal brain development (Jolles et al, 2011), migraine (Wang et al, 2022), mild cognitive impairment (Gao et al, 2022c), and Parkinson's Disease (Mi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%